Improving Restoration Programs Through Greater Connection With Ecological Theory and Better Monitoring - Lindenmayer, David (Frontiers in Ecology and Evolution, 2020)
The United Nations proclaimed 2019-2029 as the decade of landscape restoration. This is an exciting and necessary initiative. However, past restoration efforts have often been less than effective, as they either have not been monitored, or have been subjected to poor quality monitoring and not linked with ecological concepts and/or theory. These deficiencies make it difficult to: (1) identify general principles for broader application beyond site-specific insights, (2) quantify success, and (3) identify general ways to improve restoration programs. The potential for learning has been further impaired by a generally risk averse attitude to restoration, where opportunities for testing and then reporting new approaches have been limited, and chances to learn from mistakes have sometimes not occurred. These problems need to be rectified if future restoration programs are to be more successful than those in the past and are to deliver better ecological returns on investment. This should help enhance learning and boost the potential for continuous improvement in restoration efforts.